2017
DOI: 10.5433/1679-0359.2017v38n2p1017
|View full text |Cite
|
Sign up to set email alerts
|

Energy and tannin extract supplementation for dairy cows on annual winter pastures

Abstract: Energy supplementation can increase the consumption of metabolizable energy and substrate for microbial growth, while condensed tannins aid in increasing the duodenal flow of metabolizable proteins. The objective of this study was to evaluate the effects of energy supplementation and the inclusion of tannin extract (TE) from Acacia mearnsii (Weibull Black, Tanac S. A., Montenegro, Brazil) on the production performance of dairy cows grazing on winter pastures. Nine multiparous Holstein cows in mid lactation wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 12 publications
2
9
0
2
Order By: Relevance
“…There was no effect of TA on milk production or composition in the present study, which was in accordance with results reported in similar studies with dairy cows supplemented with 3.4–12.0 g/kg DM of TA (Alves et al., 2017; Griffiths et al., 2013). As a normal physiological process, dairy cows mobilize energy from body tissues to support energy requirements for milk production during early lactation and replete mobilized tissue reserves during mild and late lactation for the subsequent lactation (NRC, 2001).…”
Section: Discussionsupporting
confidence: 93%
“…There was no effect of TA on milk production or composition in the present study, which was in accordance with results reported in similar studies with dairy cows supplemented with 3.4–12.0 g/kg DM of TA (Alves et al., 2017; Griffiths et al., 2013). As a normal physiological process, dairy cows mobilize energy from body tissues to support energy requirements for milk production during early lactation and replete mobilized tissue reserves during mild and late lactation for the subsequent lactation (NRC, 2001).…”
Section: Discussionsupporting
confidence: 93%
“…When dairy cows were supplemented with tannin extract of Acacia mearnsii from 10.9 to 19.1 g/kg of diet DM, decreased urinary N excretion were observed, albeit in addition to negative effects on feed intake and milk yield (Grainger et al, 2009). However, milk yield did not change with inclusions below 11.0 g/ kg of diet DM (Griffiths et al, 2013;Alves et al, 2017), but neither digestibility nor urinary N excretion was evaluated in these studies.…”
Section: Introductionmentioning
confidence: 81%
“…Cows produced 7,320 kg (SD = 1,044) of milk yield in the previous lactation, and at the start of period 1, cows had an average BW of 546 kg (SD = 34), milk production of 23 kg (SD = 2.6), and were 197 DIM (SD = 12). The experiment was conducted throughout 3 successive 22-d periods, with 14 ) to determine the sample size required to detect a difference of 1 kg of milk produced, with a type I error (α) = 0.05 and a power of 80% (Festing and Altman, 2002), based on previous studies of the team and published information (Griffiths et al, 2013;Mendoza et al, 2016a,b;Ueda et al, 2016;Alves et al, 2017). The treatments tested within each Latin square consisted of a combination of PMR and 1 grazing session of 5 h, as follows: (1) morning grazing session and afternoon PMR meal (AM); (2) afternoon grazing session and morning PMR meal (PM); and (3) morning grazing session and afternoon PMR meal supplemented with 15.0 g of tannins/kg of PMR DM (TAN).…”
Section: Animals Experimental Design and Treatmentsmentioning
confidence: 99%
“…This result is because the circulating amino acids that exceed the productive capacity of the animals can be deaminated, and N can be excreted in the urine in the form of urea. In this respect, it has been shown that the tannin extract had no significant effect on the yield and chemical composition of milk in dairy cows (ALVES et al, 2017). In contrast, cattle fed diets containing soybean meal or canola meal combined with 1.5% of the tannin extract of Acacia mearnsii presented an increase in the intestinal flow of α-amino N and non-ammonia non-microbial N, whereas the intestinal flow of microbial N and the efficiency of microbial protein synthesis were not affected (ÁVILA, 2013).…”
Section: Itemsmentioning
confidence: 97%